2015
DOI: 10.1371/journal.pone.0118721
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Prenatal Alcohol Exposure Enhances GluN2B Containing NMDA Receptor Binding and Ifenprodil Sensitivity in Rat Agranular Insular Cortex

Abstract: Prenatal exposure to alcohol affects the expression and function of glutamatergic neurotransmitter receptors in diverse brain regions. The present study was undertaken to fill a current gap in knowledge regarding the regional specificity of ethanol-related alterations in glutamatergic receptors in the frontal cortex. We quantified subregional expression and function of glutamatergic neurotransmitter receptors (AMPARs, NMDARs, GluN2B-containing NMDARs, mGluR1s, and mGluR5s) by radioligand binding in the agranul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 120 publications
1
19
2
Order By: Relevance
“…We have observed a regionally-specific increase in GluN2B-containing NMDA receptor binding based on radiohistochemical studies in rats exposed to ethanol during gestation [53]. Further, in the same study, we demonstrated that evoked NMDA currents from layer II/III pyramidal neurons in AIC in PAE rats are more sensitive to the effects of ifenprodil, a negative allosteric modulator of GluN2B containing NMDA receptors, than saccharin controls.…”
Section: Introductionmentioning
confidence: 55%
“…We have observed a regionally-specific increase in GluN2B-containing NMDA receptor binding based on radiohistochemical studies in rats exposed to ethanol during gestation [53]. Further, in the same study, we demonstrated that evoked NMDA currents from layer II/III pyramidal neurons in AIC in PAE rats are more sensitive to the effects of ifenprodil, a negative allosteric modulator of GluN2B containing NMDA receptors, than saccharin controls.…”
Section: Introductionmentioning
confidence: 55%
“…Other highly disturbed is the glutamatergic system, mainly the regionally specific glutamate receptor expression (Bird et al, 2015). Particularly, NMDA receptor subunits are affected.…”
Section: Key Neurotransmitters Systems Are Affected In Pae and Adhdmentioning
confidence: 99%
“…Also, a functional NMDA-NR1 receptors are necessary for the neurotoxic and teratogenic effects of PAE (Deng and Elberger, 2003). Additionally, synaptic NR2B-containing NMDA receptor concentrations are reduced in PAE animals (Samudio-Ruiz et al, 2010), specifically in the agranular insular cortex (Bird et al, 2015). Taken together, these evidences could help to explain EtOH-related alterations in learning and behaviors that depend on cerebral cortex.…”
Section: Key Neurotransmitters Systems Are Affected In Pae and Adhdmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study [20] we replicated the effect of moderate PAE on male social behavior and observed impaired motor behaviors (tongue protrusion [78, 79]), and decreased behavioral flexibility as measured by increases in perseverative errors in the Morris water task. This collection of deficits was of particular interest based on commonalities in the ventrolateral frontocortical circuitry required for these behaviors and reports of alterations in ventrolateral frontal cortex function following moderate PAE [6, 19, 22]. …”
Section: Introductionmentioning
confidence: 99%